Phychchemical Studies and Antifngal Activity of Ulva Rigida C.A.G SP (Chlorophya) from Coast of Karachi Pakistan - Samina Kabir S. Akbar, Amina Kabir Khanzada (International Journal of Modern Agriculture, 2021)
The green alga Ulva rigida c.A,g sp(Chlorophycota) collected from the coast of Karachi, Pakistan, has been allocated for the fatty acid composition. Acid was changed to methyl esters and identified GC - MS. The 3,Saturated, 23 Unsaturated fatty acids was present, The top saturated fatty acids was present n-Hexadecanoate (8.17%) and lowermost saturated fatty acids was n-Docosanoate, (3.14%.) the Unsaturated fatty acid are maximum percentage in Methyl-tricosenote15.01%,10 Octadecenoicacid 10.81% , Hexadecanoic acid 7.87%, Heptadecenoate 7.15% and smallest amount n-Heptaecenoic acid 0.03% , 3,8-Dimethyl-27-nonadicneate ,0.41% ,in which 7 are mnonic ,4 are Dieonoic and 5 are trienoic fatty acids were originate . The antifungal activity in A. Niger in Ethanol extract 85.71% and P.funiculosum in Chloroform extract 78% and minimum inhibition activity against A. niger 28.57% in Aqueous extract was observed . and Magnesium (Mg) 3179.58 mg/kg Potassium (K )21248.8 mg/kg Calcium (Ca) 10751, mg/kg and Chromium (Cr) was present in lowest amount 0.65mg/kg and protein in the range 14.34% in Sandpits, Bulaji village 20.6 % and minimum in Hawk’s bay 12.46%